The Influence of Gout Sufferers' Uric Acid Levels On Boiled Water Soursop Leaves (Annona Muricata) - Nur Soemah, Eka; Emyk Windartik (Kirana Publisher (KNPub), 2022)
This study sought to ascertain the impact of administering cooked water Soursop leaves (Annona muricata) to gout patients in the village of Plososari Mojokerto on their uric acid levels. This study's design was not experimental. All of the 20 plososari mojokerto individuals with gout made up the study's population. Total sampling is the sample method used in this study. According to the findings of statistical testing, there was a drop in uric acid levels before and after, with 20 (100%) of the respondents having high levels before, 10 (50%) after, and 10 (50%) of the remaining respondents having normal levels. One that results from their excessive consumption of purine-rich foods.